Infrageneric placement of the Southern Hemisphere taxa of Anemonastrum and Knowltonia earlier included in Anemone sensu lato (Ranunculaceae) - Mosyakin, S.L.; de Lange Peter J.; Bulakh, O.V. (Український ботанічний журнал, 2018)
The genera Anemonastrum and Knowltonia earlier usually included in Anemone sensu lato (Ranunculaceae: Anemoneae) were recently proposed to be recognized in expanded circumscriptions, based on molecular phylogenetic findings and partly also morphological and biogeographical evidence. Both these genera contain some representatives that are noteworthy from morphological and biogeographical viewpoints, and the general ranges of these genera (combining the ranges of their included species) demonstrate remarkable continent-scale disjunctions. In particular, Knowltonia in its new circumscription (corresponding to Anemone sect. Pulsatilloides sensu Hoot et al., 2012) contains southern African and some American taxa (mostly South American ones, including Oreithales, Barneoudia, etc.), and K. crassifolia from Tasmania. Anemonastrum (corresponding to Anemone subg. Anemonidium sensu Hoot et al., excluding Hepatica) is mainly Eurasian, but it also includes several North American species, as well as A. antucense from southern South America and A. tenuicaule from New Zealand. Species of the newly outlined Anemonastrum and Knowltonia were placed in various infrageneric taxa of Anemone sensu lato. Following the re-circumscription of genera, it is now timely to nomenclaturally update and partly re-circumscribe the relevant infrageneric taxa earlier treated in Anemone sensu lato. Here we propose the following new combinations at the section and subsection ranks: Knowltonia sect. Mexicanae (Starod.) Mosyakin & de Lange, comb. nov. (incl. K. mexicana); sect. Crassifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. crassifolia); sect. Rigidae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. Knowltonia hootae = Anemone rigida, K. hepaticifolia, K. moorei); sect. Meridium (Starod.) Mosyakin & de Lange, comb. nov. (incl. K. helleborifolia and K. peruviana), sect. Sellowiae (Hoot) Mosyakin & de Lange, comb. nov. (incl. K. sellowii and K. assisbrasiliana); sect. Oreithales (Schltdl.) Mosyakin & de Lange, comb. nov. (incl. K. integrifolia); sect. Barneoudia (Gay) Mosyakin & de Lange, comb. nov. (incl. K. balliana, K. chilensis, K. major); sect. Pulsatilloides (DC.) Mosyakin & de Lange, comb. nov.; [sect. Pulsatilloides] subsect. Alchemillifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. caffra and K. fanninii), and [sect. Pulsatilloides] subsect. Pinnatifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. tenuifolia). The new species-rank combination Knowltonia caffra (Eckl. & Zeyh.) Christenh. & Byng ex Mosyakin & de Lange, comb. nov. is validated. The new subsectional name Anemonastrum sect. Anemonidium subsect. Makariri de Lange & Mosyakin, subsect. nov. is proposed; this new subsection houses Anemonastrum antucense from South America and A. tenuicaule from New Zealand. На основі молекулярно-філогенетичних і частково також морфологічних та біогеографічних даних нещодавно було запропоновано визнати у значно розширеному розумінні роди Anemonastrum та Knowltonia, які раніше здебільшого включали до Anemone sensu lato ( Ranunculaceae). Обидва ці роди включають представників, які є цікавими з морфологічної та біогеографічної точок зору, а загальні ареали цих родів (тобто, сума ареалів їхніх видів) демонструють явні міжконтинентальні диз'юнкції. Зокрема, Knowltonia в новому розумінні (що відповідає Anemone sect. Pulsatilloides sensu Hoot et al., 2012) включає південноафриканські та деякі американські (переважно південноамериканські) таксони, а також K. crassifolia з о-ва Тасманія. Рід Anemonastrum (що відповідає Anemone subg. Anemonidium sensu Hoot et al., за виключенням роду Hepatica) є переважно євразійським, але також містить декілька північноамериканських видів та південноамериканський A. antucense і новозеландський A. tenuicaule. Види, що зараз включені до Anemonastrum та Knowltonia, раніше розміщували в різних внутрішньородових таксонах роду Anemone sensu lato. Тепер ці внутрішньородові таксони мають бути дещо переглянуті та перенесені до відповідних родів. Ми пропонуємо в статті такі нові комбінації рангів секції та підсекції: Knowltonia sect. Mexicanae ( Starod.) Mosyakin & de Lange, comb. nov. (incl. K. mexicana); sect. Crassifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. crassifolia); sect. Rigidae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. Knowltonia hootae ≡ Anemone rigida, K. hepaticifolia, K. moorei); sect. Meridium (Starod.) Mosyakin & de Lange, comb. nov. (incl. K. helleborifolia та K. peruviana), sect. Sellowiae (Hoot) Mosyakin & de Lange, comb. nov. (incl. K. sellowii та K. assisbrasiliana); sect. Oreithales (Schltdl.) Mosyakin & de Lange, comb. nov. (incl. K. integrifolia); sect. Barneoudia (Gay) Mosyakin & de Lange, comb. nov. (incl. K. balliana, K. chilensis, K. major); sect. Pulsatilloides (DC.) Mosyakin & de Lange, comb. nov., [sect. Pulsatilloides] subsect. Alchemillifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. caffra та K. fanninii), [sect. Pulsatilloides] subsect. Pinnatifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. tenuifolia). Валідизована нова комбінація у ранзі виду, Knowltonia caffra (Eckl. & Zeyh.) Christenh. & Byng ex Mosyakin & de Lange, comb. nov. Описана нова підсекція Anemonastrum sect. Anemonidium subsect. Makariri de Lange & Mosyakin, subsect. nov.; ця підсекція містить Anemonastrum antucense з Південної Америки та A. tenuicaule з Нової Зеландії. На основе молекулярно-филогенетических и частично также морфологических и биогеографических данных недавно было предложено признать в значительно расширенном понимании роды Anemonastrum и Knowltonia, которые ранее преимущественно включали в род Anemone sensu lato (Ranunculaceae). Оба эти рода включают представителей, которые интересны с морфологической и биогеографической точек зрения, а ареалы этих родов (то есть, сумма ареалов их видов) демонстрируют явные межконтинентальные дизъюнкции. В частности, Knowltonia в новом понимании (соответствующем Anemone sect. Pulsatilloides sensu Hoot et al., 2012) включает южноафриканские и некоторые американские (преимущественно южноамериканские) таксоны, а также K. crassifolia из о-ва Тасмания. Род Anemonastrum (соответствующий Anemone subg. Anemonidium sensu Hoot et al., за исключением рода Hepatica) преимущественно евразийский, но он также включает несколько североамериканских видов, южноамериканский A. antucense и новозеландский A. tenuicaule. Виды, которые сейчас включены в Anemonastrum и Knowltonia, ранее размещали в различных внутриродовых таксонах рода Anemone sensu lato. Теперь эти внутриродовые таксоны должны быть несколько пересмотрены и перенесены в соответствующие роды. Мы предлагаем здесь следующие новые номенклатурные комбинации рангов секции и подсекции: Knowltonia sect. Mexicanae (Starod.) Mosyakin & de Lange, comb. nov. (incl. K. mexicana); sect. Crassifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. crassifolia); sect. Rigidae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. Knowltonia hootae ≡ Anemone rigida, K. hepaticifolia, K. moorei); sect. Meridium ( Starod.) Mosyakin & de Lange, comb. nov. (incl. K. helleborifolia и K. peruviana), sect. Sellowiae (Hoot) Mosyakin & de Lange, comb. nov. (incl. K. sellowii и K. assisbrasiliana); sect. Oreithales ( Schltdl.) Mosyakin & de Lange, comb. nov. (incl. K. integrifolia); sect. Barneoudia (Gay) Mosyakin & de Lange, comb. nov. ( incl. K. balliana, K. chilensis, K. major); sect. Pulsatilloides (DC.) Mosyakin & de Lange, comb. nov., [sect. Pulsatilloides] subsect. Alchemillifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. caffra и K. fanninii), [sect. Pulsatilloides] subsect. Pinnatifoliae (Ulbr.) Mosyakin & de Lange, comb. nov. (incl. K. tenuifolia). Действительно обнародована новая комбинация в ранге вида, Knowltonia caffra (Eckl. & Zeyh.) Christenh. & Byng ex Mosyakin & de Lange, comb. nov. Описана новая подсекция Anemonastrum sect. Anemonidium subsect. Makariri de Lange & Mosyakin, subsect. nov.; эта подсекция включает Anemonastrum antucense из Южной Америки и A. tenuicaule из Новой Зеландии.